2013
DOI: 10.1007/s00784-013-1037-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the erosive potential of viscosity-modified soft acidic drinks on enamel

Abstract: OBJECTIVE: The objective of this in vitro study was to investigate the effect of viscositymodified soft acidic drinks on enamel erosion. MATERIALS AND METHODS: A total of 108 bovine enamel samples ( = 3 mm) were embedded in acrylic resin and allocated into six groups (n = 18). Soft acidic drinks (orange juice, Coca-Cola, Sprite) were used both in their regular forms and at a kinetic viscositiy of 5 mm(2)/s, which was adjusted by adding hydroxypropyl cellulose. All solutions were pumped over the enamel surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Erosive wear has become a prevalent oral health problem, affecting an increasing proportion of the population worldwide 1 . Erosive wear can be influenced by many factors, including biological factors, particularly saliva and the acquired enamel pellicle (AEP), which may have an important role in the prevention and/or progression of erosion 2 6 . However, the difficulty of modelling dental erosion in vitro has led to many conflicting reports and much confusion in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Erosive wear has become a prevalent oral health problem, affecting an increasing proportion of the population worldwide 1 . Erosive wear can be influenced by many factors, including biological factors, particularly saliva and the acquired enamel pellicle (AEP), which may have an important role in the prevention and/or progression of erosion 2 6 . However, the difficulty of modelling dental erosion in vitro has led to many conflicting reports and much confusion in this field.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,15 Most studies have been performed in vitro; therefore, the results observed may be only due to the effects of pH and titratable acidity of the drink itself, without considering salivary clearance. Moreover, in many studies assessing the erosive potential of acidic beverages 13,16,17,18,19 or other dietary substances and medications, 3 the counter effects of salivary clearance and buffering have not been considered. Our results showed that the salivary pH recovery is affected by the titratable acidity of the beverages, which should be considered in the models that study erosion.…”
Section: % Sucrosementioning
confidence: 99%
“…Mineral loss and erosion of tooth hard structure can be intensified by consumption of acidic food and drinks (10,11). So, the interaction of bleaching agents with intake of acidic drinks could intensify the damage on enamel surface (10,12).…”
Section: Introductionmentioning
confidence: 99%